Investigating the heterogeneity of economic convergence in Latin America countries: An econometric analysis of systems of regression equations - Dawid Jarco; Mateusz Pipien (Latin American Economic Review, 2020)
For a selected group of Latin America countries we estimated the parameters of convergence equations on the basis of annual data. We test cross-country heterogeneity of parameters within a system of Seemingly Unrelated Regression Equations (SURE) that departures from standard approach utilizing panel regressions. We show empirical evidence in favor of the variability of parameters describing the convergence effect and productivity growth rates across analyzed club of countries. We also test several restrictions leading to less parameterized models imposing constancy of parameters of interest across countries.
Keywords: C30; C47; 330; convergence; labour productivity; economic growth; SURE; Latin America